Deep Penetration Welding of 12-mm Thick Section Steels with No Groove by Plasma-Gmaw Hybrid Welding Process - Tran, Lam (Old Journal, 2019)
Hybrid welding processes were developed several decades ago and nowadays, it becomes a bright technology in materials processing. In recent years, one of the versions of the Plasma – GMAW hybrid welding process is basically a combination of a Plasma keyhole with a GMAW arc, where the GMAW arc emitted from the side‐posited tungsten toward the nozzle orifice, the consumable wire fed along the torch axis through the orifice, in order to deliver greater welding speeds, deeper weld penetration, and reduced heat input. In this paper, butt joint welds were conducted on mild steel SS400 and the aims of this research is developed a Plasma‐GMAW hybrid welding process for single pass full penetration welding of 12‐mm thick mild steel with no groove of thick steel plates. As a result, the single‐sided welding in one pass with complete penetration was produced successfully and their mechanical properties were investigated.